1983
DOI: 10.1111/j.1600-065x.1983.tb00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease Associations with Complotypes, Supratypes and Haplotypes

Abstract: We have used the term supratype to describe combinations of alleles and have examined associations with disease. In RA and insulin-dependent diabetes one or more supratypes appear to be important but their functional significance remains obscure. In MG and SLE the HLA supratype may contain loci involved in immunoregulation, complement synthesis and hormone metabolism. MG induced by D-Pen is associated with Bw35/DR1 rather than A1, B8, DR3. In contrast there is no evidence of a supratype in AS. We have proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
129
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(139 citation statements)
references
References 13 publications
9
129
1
Order By: Relevance
“…These data support our previous suggestion, based on analysis of class I1 antigens, that genetic factors involved in the development of primary SS might differ from those in secondary SS (11). In Caucasians, SS is associated with a haplotype marked by HLA-B8 and DR3, which also contains C4AQO (4,6,7,9,10). Therefore, C4AQO itself may influence susceptibility to the development of primary SS in both Caucasian and Japanese individuals.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These data support our previous suggestion, based on analysis of class I1 antigens, that genetic factors involved in the development of primary SS might differ from those in secondary SS (11). In Caucasians, SS is associated with a haplotype marked by HLA-B8 and DR3, which also contains C4AQO (4,6,7,9,10). Therefore, C4AQO itself may influence susceptibility to the development of primary SS in both Caucasian and Japanese individuals.…”
Section: Discussionsupporting
confidence: 89%
“…It is well established that individuals carrying null alleles of C4 are more susceptible to many HLAassociated diseases, such as SLE, SSc, subacute sclerosing panencephalitis, RA, and Felty's syndrome (6,7,(18)(19)(20)(21). Both C4A and C4B proteins are known to participate in the generation of the classical pathway component C3 convertase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no HLA-transgenic mouse models that express multiple linked genes from common autoimmuneprone human haplotypes. There is considerable evidence that haplotypic combinations of genes within the MHC play an important role in autoimmunity (4,12). Haplotypes potentially contribute to disease phenotype through the sum of the interactions between individual gene products and their coregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although population data (7) and studies of transgenic mice (8,9) have identified some of the individual genes that are responsible for disease susceptibility in MHC haplotypes, some studies conclude that disease risk is conferred by combinations of HLA DR and DQ genes (6, 10 -13) and may involve genes within the class III region of the MHC (12,14). This has led to suggestions that disease susceptibility may depend upon the MHC haplotype context rather than any particular gene within the haplotype (4,6). Of the HLA haplotypes associated with autoimmunity the class II HLA DR3-DQ2 haplotype is particularly prominent in that it is linked to an increased risk of insulin-dependent diabetes, thyrogastric autoimmunity, systemic lupus erythematosus, Sjögren's syndrome, myasthenia gravis, celiac disease, and many other autoimmune conditions (3,12).…”
mentioning
confidence: 99%